Halogen atom effect on the photophysical properties of substituted aza-BODIPY derivatives. Issue 3 (6th January 2017) - De Simone, B. C.; Mazzone, G.; Pirillo, J.; Russo, N.; Sicilia, E.
Abstract : The influence of halogen atom substitution (Br and I), in different amounts and positions in an aza-BODIPY skeleton, on the photophysical properties of some aza-BODIPY derivatives has been investigated by using density functional theory and its time-dependent extension. Abstract : The influence of halogen atom substitution (Br and I), in different amounts and positions in an aza-BODIPY skeleton, on the photophysical properties of some aza-BODIPY derivatives has been investigated by using density functional theory and its time-dependent extension. The heavy atom effect on excitation energies, singlet–triplet energy gaps and spin–orbit matrix elements has been considered. The maximum absorption within the therapeutic window has been confirmed for all the aza-BODIPY derivatives. The feasible intersystem spin crossing pathways for the population of the lowest triplet state, that will depend on the values of the spin–orbit matrix elements, the energy gap as well as the orbital composition of the involved states have been found to most likely involve the S1 and T1 or T2 states. The outcomes of computations support the potential therapeutic use of these compounds as photosensitizers in photodynamic therapy.